Use of a double pigtail ureteral stent for surgical management of obstructive pancreatolithiasis in a feline patient - Lydia Chang; Jim A Taylor (Journal of Feline Medicine and Surgery Open Reports)
Case summary A 7-year-old castrated male domestic shorthair cat was presented for surgical intervention for obstructive pancreatolithiasis. The patient had a history of chronic weight loss, vomiting and lethargy. Elevation of feline pancreas-specific lipase and a marked decrease in cobalamin were documented on blood biochemistry. Abdominal ultrasound revealed an enlarged right pancreatic limb with a dilated central duct and multiple pancreatoliths visualized within, consistent with partial pancreatic duct obstruction. The patient was successfully treated with a minor duodenal papilla construction using a 2.5 Fr double pigtail ureteral stent. Relevance and novel information Pancreatolithiasis is an exceptionally rare condition in veterinary medicine, particularly in cats, with only a few reported cases. Given its low incidence, there is no established consensus regarding the best therapeutic options in clinical practice. This case report outlines the successful application of a locking loop catheter to re-establish the patency of a pancreatic duct. Notably, this is the first documented use of this technique for the surgical management of obstructive pancreatolithiasis.